Prevention of Mastitis and Reduction of Microbial Contamination of Cow Milk - A. Larionov, Gennady; G. Semenov, Vladimir; Yu. Lavrentyev, Anatoly; V. Mardaryev, Nataliya (International Journal of Engineering and Technology, 2018)
It is necessary to strictly follow the technology, veterinary and sanitary rules of milking, perform well-timed diagnostics and treatment of cows during the production of milk. The main causes of poor quality are high bacterial contamination and high content of somatic cells in milk. In this connection, treatment of cows’ udder tits with modern and disinfecting solutions was checked through scientific and industrial experiments in the conditions of a dairy farm. There were three groups of cows (1st and 2nd - experimental, 3rd - control); they consisted of 10 animals, which were uniform in breed (black-and-white), age (3-4 years), calving time, and body weight. The quality of cow milk was also homogeneous in terms of the physical and chemical parameters: the mass fraction of protein and fat, dry matter, acidity and density. At the beginning of the studies, the microbial contamination of milk was 3,800,000 cfu/ml, the number of somatic cells was 400,000 in 1 ml in all groups; this did not meet modern requirements. To reduce microbial contamination and the number of somatic cells in milk, the udder was treated before and after milking. The taken measures led to the improvement of the quality of milk in terms of microbial contamination and the number of somatic cells.